(untitled) (Research, Society and Development, 2022)
This article is a study about the changes in high school education - which is the last stage of basic education in Brazil - and the education that is intended to be integral to teenagers and young people, especially those from the working class. For this purpose, polytechnic formation was taken as a model of comprehensive training, conceived by Karl Marx for the education of working-class youth and the ideal training for social transformation. It was elaborated by a questioning about public policies in the proposal of the new model of high school (Federal Law nº 13.415/17) for an integral formation, this study aims to reveal the characteristics of a polytechnic integral education; discuss Marx and Engels’ conceptions about the integral education of teenagers and young people and training for work; also think on the influence of capitalism in The Education for All Movement on Brazilian public educational policies since the 1990s. As a methodology, the ontological approach was used (historical-dialectical materialism), whose nature of the research departs from objectivity to subjectivity, in a bibliographical consultation between books and academic articles whose authors deal with themes related to polytechnic education, new high school, work and youth education. The results indicate that the new high school would not be able to meet the needs of the working class, since, dominated by capitalism, it constitutes an education for permanence in the conditions of dominators and dominated, among other aspects.